2010
DOI: 10.1155/2010/934694
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Recombinant Dengue-2 Virus Derived from a Single Nucleotide Substitution in the 5′ Noncoding Region

Abstract: Variants of wild-type dengue serotype 2 (DEN-2) virus containing nucleotide substitutions at positions 14, 15, or 57 in the 5′ NCR were constructed by PCR-mediated site-directed mutagenesis. All three viruses containing a single point substitution demonstrated attenuation phenotype as evidenced by decreases replication and plaque size in cell culture assay. All three variants were less neurovirulent in newborn mice compared to the wild type. The mutants were immunogenic in adult mice immunogenicity and maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 22 publications
2
17
0
2
Order By: Relevance
“…Using the Δ-DENV/GFP replicons, we were able to dissect the mutation effects of seven 5′NCR mutations that we have previously analyzed using the infectious clone system (Leardkamolkarn et al, 2010;Sirigulpanit et al, 2007). Our results suggested that deletion of nt 57 or 57-58 severely diminished the GFP expression and RNA replication.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Using the Δ-DENV/GFP replicons, we were able to dissect the mutation effects of seven 5′NCR mutations that we have previously analyzed using the infectious clone system (Leardkamolkarn et al, 2010;Sirigulpanit et al, 2007). Our results suggested that deletion of nt 57 or 57-58 severely diminished the GFP expression and RNA replication.…”
Section: Discussionmentioning
confidence: 77%
“…Supernatants of the transfected cells collected on days 1, 4, 6 and 8 pt were determined for infectious viral titer by standard plaque titration assay as previously described (Leardkamolkarn et al, 2010). Briefly, 200 µl of serially diluted supernatant was inoculated onto the confluent monolayer of BHK-21 cells.…”
Section: Analysis Of Virion Productionmentioning
confidence: 99%
See 3 more Smart Citations